Navigating menstrual stigma and norms: a qualitative study on young people’s menstrual experiences and strategies for improving menstrual health - Eva Åkerman; Anna Wängborg; Maria Persson; Renita Sörensdotter; Marie Klingberg-Allvin (BMC Public Health)
Abstract Background Menstrual health is a recognised important public health issue and is essential for the realisation of gender equality and the achievement of Sustainable Development Goals. This study aimed to explore the menstrual health experiences of young people in Sweden and how the menstrual cycle affects their health and lives. The study also aimed to identify the facilitators and barriers to achieving menstrual health. Methods We conducted a qualitative study in Sweden. Sixteen young people aged 18–28 who have experienced the menstrual cycle participated in individual interviews. Purposeful sampling combined with snowball sampling was applied to recruit the participants. The data were analysed using reflexive thematic analysis. Results Participants viewed menstruation as a sign of having a healthy and functioning body. Menstruation was linked to becoming a woman and fostered a sense of community and sisterhood, which was viewed as positive among cis women. Further, the results showed that physical and emotional symptoms related to the menstrual cycle limited the participants’ everyday lives and social relationships and had a negative effect on their sexual and mental health. While managing their emotional discomfort and other menstrual complaints, they also had to deal with the public stigma and norms about menstruation contributing to shame and worries. Barriers to menstrual health included stigma and norms related to menstruation, which led to the adoption of expected behaviours, such as avoiding participation in social activities. The normalisation of menstrual complaints also contributed to delays in seeking healthcare, despite having symptoms that had a negative effect on their health. An important factor promoting menstrual health and quality of life is access to prompt treatment to mitigate and decrease symptoms that limit everyday life. Conclusions The results indicate that menstrual stigma and related norms create challenging situations limiting menstruating people’s everyday lives and reluctance to seek healthcare despite needing to. To promote the menstrual health of menstruating young people in Sweden, organised and systematic screening of menstrual cycle-related symptoms should be provided within student health services at schools and universities, and primary healthcare. Policymakers should consider integrating stigma-reducing efforts into public health interventions to improve general awareness and promote gender equality.